The effect of autologous platelet-rich plasma intrauterine perfusion on pregnancy outcomes of frozen-thawed embryo transfer in patients with chronic endometritis - Chen, Lili; Liu, Lan; Guo, Huanhuan; Wang, Zhenhua (Frontiers in Reproductive Health, 2025)
ObjectiveTo analyze the effect of autologous platelet-rich plasma (PRP) intrauterine perfusion on the clinical outcomes of frozen-thawed embryo transfer in patients with chronic endometritis.MethodsA retrospective continuous cohort of 219 patients diagnosed with chronic endometritis at the Reproductive Medicine Center of Affiliated Hospital of Putian University between January 2020 and December 2022, undergoing their first frozen-thawed embryo transfer cycle, was included. All patients received standardized oral doxycycline treatment after diagnosis. Based on whether they received PRP intrauterine perfusion prior to embryo transfer, patients were divided into an observation group (PRP group, n=103) and a control group (non-PRP group, n = 116). Outcome measures included live birth rate per transfer cycle, clinical pregnancy rate per transfer cycle, and early miscarriage rate per clinical pregnancy.ResultsAll patients underwent endometrial preparation using a hormone replacement therapy (HRT) protocol. Endometrial thickness on the day before transformation was significantly higher in the PRP group compared to the control group (10.58 ± 1.78 mm vs. 9.79 ± 1.58 mm, P = 0.001). The PRP group exhibited significantly higher clinical pregnancy rate per transfer cycle and live birth rate per transfer cycle than the control group (58.25% vs. 40.52%, P = 0.038; 52.43% vs. 34.48%, P = 0.007). The difference in early miscarriage rate per clinical pregnancy between the PRP group and the control group was not statistically significant (8.33% vs. 14.89%, P = 0.86). The live birth rate per transfer cycle in the single-PRP subgroup was significantly lower than in the multiple-PRP subgroup (44.62% vs. 65.79%, P = 0.038). There were no statistically significant differences in clinical pregnancy rate per transfer cycle or early miscarriage rate per clinical pregnancy between the single-PRP and multiple-PRP subgroups (52.31% vs. 68.42%, P = 0.110; 11.76% vs. 3.85%, P = 0.377).ConclusionFor patients diagnosed with chronic endometritis undergoing their first frozen-thawed blastocyst transfer after standardized antibiotic treatment, adjunctive PRP intrauterine perfusion therapy improves pregnancy outcomes.